ΘS-cyclic codes over Ak. Issue 1 (2nd January 2016) - , Irwansyah; Barra, Aleams; Dougherty, Steven T.; Muchlis, Ahmad; Muchtadi-Alamsyah, Intan; Solé, Patrick; Suprijanto, Djoko; Yemen, Olfa
ABSTRACT: We study -cyclic codes over the family of rings . We characterize -cyclic codes in terms of their binary images. A family of Hermitian inner-products is defined and we prove that if a code is -cyclic then its Hermitian dual is also -cyclic. Finally, we give constructions of -cyclic codes.